Education, learning, training: Critical issues for development - Gilles Carbonnier; Michel Carton; Kenneth King (Brill Nijhoff, 2014)
In Education, Learning, Training: Critical Issues for Development, renowned scholars and practitioners examine shifts in global education policy and practice over the last 50 years.
Keywords: 320; Bildungspolitik; Entwicklungspolitik; Lebenslanges Lernen; Weiterbildung; Entwicklungshilfe; China; Entwicklung; Afrika